Advanced dual-sided microstructured semiconductor neutron detectors and instrumentation - Ochs, Taylor R. (Kansas State University, 2020)
Dual-Sided Microstructured Semiconductor Neutron Detectors (DS-MSNDs) have been developed as a viable alternative to expensive ³He for thermal-neutron detection. DS-MSNDs were designed as an advancement on single-sided MSNDs which comprise high-aspect ratio trenches backfilled with ⁶LiF neutron conversion material etched deep into silicon pvn-junction diodes. Neutrons react in the conversion material, which produces energetic charged-particle reaction products that are measured in the adjacent silicon microfeatures. Single-sided MSNDs have been produced with an intrinsic thermal-neutron detection efficiency of 30-35% for normally incident neutrons, and the key limiting factor in detection efficiency is neutron free streaming paths through the neutron insensitive silicon fins. The DS-MSND incorporates a second set of ⁶LiF-backfilled trenches etched on the back-side of a thicker silicon diode that are offset from the front-side trenches to eliminate the neutron free streaming paths. Monte Carlo simulations show DS-MSNDs only 1.5-mm thick are theoretically capable of 80% intrinsic thermal-neutron detection efficiency, which could directly match commonly available ³He detectors. This work describes the design of DS-MSNDs including electric field modeling and microfeature geometry optimization with MCNP simulations, and fabrication process improvements implemented that elevate the state-of-the-art. The previous world record for intrinsic thermal-neutron detection efficiency for semiconductor neutron detectors was 53.5 ± 0.6%. Advancements in deep-trench etching and ⁶LiF backfilling methods presented herein have increased the current record intrinsic-thermal neutron detection efficiency to 69.3 ± 1.5%. Several prototype detector systems were fabricated implementing DS-MSND and MSND technology to aid in search and localization of special nuclear material. Drop-in replacements for small-diameter, high-pressure ³He detectors, and the DS-MSND-based HeRep Mk IV measured 80% to 115% of the count rate of a similarly sized 10-atm ³He detector based on the detector and source moderation configuration. Additionally, modular neutron detectors were developed for use in a high-sensitivity, low profile, wearable neutron detector for covert or overt source detection missions by warfighters, first responders, or law enforcement personnel. Additionally, MCNP simulations show the wearable detectors have potential to as operate as high-accuracy, real-time, neutron dose meters. The DS-MSND-based detector systems with on-board electronics offer a low-cost, low-power, compact, high sensitivity, alternative to ³He neutron detection.
Keywords: Radiation detection; Helium-3 replacement; neutron detection; solid-state detector; Monte carlo modeling; Silicon processing